Women's Experiences and Preferences for Service Delivery of Non-Invasive Prenatal Testing for Aneuploidy in a Public Health Setting: A Mixed Methods Study. - Celine Lewis; Melissa Hill; Lyn S Chitty (PLoS ONE)
Non-invasive prenatal testing (NIPT) for aneuploidy is currently only available in the UK through the private sector outside of the research arena. As part of an implementation study in the UK National Health Service we conducted a mixed methods study to assess women's experience of being offered NIPT using validated measures of decisional conflict, decisional regret and anxiety. Clinical service preferences were also explored. Women with a Down syndrome screening risk >1:1000 were invited to take part in the study and offered NIPT, NIPT and invasive testing (for women with a risk above 1:150) or no further testing. A cross-sectional survey and semi-structured interviews were conducted at two time points; at the time of testing and one month following receipt of results (or equivalent for NIPT decliners). In total, 845 questionnaires and 81 interviews were analysed. The main motivation to accept NIPT was for reassurance (30.8%). Decisional conflict occurred in a minimal number of cases (3.8%), however, none of the participants experienced decisional regret. Around a third (29.9%) of women had elevated anxiety at the time of testing, including intermediate risk women who traditionally would not be offered further testing (54.4% high risk; 20.1% medium risk), a finding supported through the qualitative interviews where prolonged or additional anxiety was found to occur in some medium risk cases. Women were overwhelmingly positive about the opportunity to have a test that was procedurally safe, accurate, reduced the need for invasive testing and identified cases of Down syndrome that might otherwise have been missed. Reassurance was identified as the main motivator for accepting NIPT, particularly amongst medium risk women, with high risk women inclined to accept NIPT to inform decisions around invasive testing. The current turnaround time for test result was identified as a key limitation. All the women interviewed thought NIPT should be adopted as part of NHS clinical practice, with the majority favouring NIPT offered as a first-line test. Our study highlights the potential that NIPT has to positively impact women's experience of prenatal testing for aneuploidy.